CT and MR Imaging Findings in Methanol Intoxication Manifesting with BI Lateral Severe Basal Ganglia and Cerebral Involvement - Eyup Camurcuoglu; Ahmet Mesrur Halefoglu (Journal of the Belgian Society of Radiology, 2022)
Our case report describes a 54-year-old man who was admitted to our hospital complaining of visual impairment with gastrointestinal and neurological symptoms. Initial computed tomography examination showed bilateral symmetric putaminal and cerebral white matter hypodensities. Evaluation of the following magnetic resonance imaging, restricted diffusion in these corresponding areas were found to be compatible with cytotoxic edema. Teaching Point: Diffusion-weighted imaging (DWI) plays a crucial role in the diagnosis of acute methanol intoxication.